The Vital Role of Sustainability Science in Medicine and Public Health and the Need to Develop Sustainability Science of Medicine and Public Health. - Singh, Amarendra N. (International Medical Journal, 2013)
The need to develop Sustainability Science of Medicine and Public Health is vital for building the current and future expanding status of Medicine and Public Health on a sound economic footing. This new science will help to strive towards present and future cost containment, while maximizing good medicine and public health care on a long term basis for all. This science, founded on evidence-based Sustainability Science will be of great help and benefit to policy makers, founders, program managers, healthcare providers, and, public and government officials. The best way to develop this new subspecialty will be for it to become part of Sustainability Science. In this way, Sustainability Science of Medicine and Public Health will become evidence and knowledge based, transdisciplinary science. This will help to make the present and future growth of medicine and public health economically viable and capable enough to provide the best healthcare throughout the world.